Developing of the Pattern of Revising the Elementary School math Curriculum based on Fullan's Approach - Reza Jafariharandi (رویکردهای نوین آموزشی)
The aim of the current research was to present the model of the elementary school math curriculum based on Fulen's approach. The method of qualitative research was using synthesis research based on the analogy model based on Klein's model. The research community included reference texts in the field of identifying educational reforms needed in order to revise the elementary school math curriculum. Based on this, 42 sources in the range of 2011 to 2024 were selected and examined in a targeted manner in order to identify the educational reforms needed in the mathematics curriculum. Stopping the sampling process was based on theoretical saturation. After extracting the concepts and also compiling the final model of their validity by 10 experts in the field of educational sciences in the fields of curriculum planning, primary education and mathematics education in Isfahan in 2023, who were purposefully selected, using the content validity ratio (CVR) method to evaluate became. The results showed the pattern of revising the elementary math curriculum based on Fulen's approach with the aim of achieving deep learning and partial goals of creating and strengthening the six global competencies in students, providing the four elements of learning design, providing learning and teaching conditions and facilitating the joint research process. It is useful and executable. Therefore, it is suggested to the officials of the Ministry of Education and Research to use the designed model in order to implement educational reforms in the mathematics curriculum of the elementary school. Introduction The survival and dynamism of societies are depend on the quality of the education system at the national and international levels, and this depends on the provision of suitable conditions for the enrichment of curricula, especially in the primary period. Therefore, according to the concerns that exist in this field, most countries of the world have allocated a huge part of their country's budget to the development of the education of this course, and experts consider the design and revision of curriculum patterns to be a useful solution to achieve the educational goals of this period. One of the most important subjects in elementary school is mathematics, which unfortunately, due to its abstract nature and little connection with the realities of life, has always caused many difficulties for students compared to other subjects. The mathematics rank of Iranian students in the Tims Test (TIMSS) has shown moderate growth in the mathematics rank of students from 1995 to 2011, but this growth stopped in 2015 and has started a sharp decline since then. This sharp drop coincided with the implementation of curriculum changes in Iran, which indicates the inadequacy of the applied changes and the need to revise existing curricula in the field of mathematics. In the field of curriculum revision, various models have been presented. Among the suggested models, Fullan's model (2013) has received a lot of attention in recent years due to its comprehensive perspective on the process of change and implementation. Therefore, the current research was conducted to provide a model for revising the elementary school math curriculum based on Fullan's point of view. Method This research was applied in terms of its purpose, and in terms of how data was collected, it was qualitative research, which was conducted by synthesis research based on the analogy model. The field of research in this section included domestic and foreign reference texts in the field of identifying educational reforms needed to revise the elementary school math curriculum. After several stages of screening, 302 sources were selected and studied among the reference texts based on the review of the title, abstract, and content. At the end, 42 studies, that were most related to the research subject in terms of content and had the necessary quality to be included in the research sample, were purposefully selected as a sample and were examined and analyzed. For this purpose, a sample of articles and specialized books were used. In the next step, the necessary information was extracted from the selected sources and the findings were categorized. After identifying the educational reforms extracted in line with the design of the model for revising the elementary mathematics curriculum, experts in the field of curriculum planning and elementary education were asked to give their opinion on each of the identified components in the form of a questionnaire with a three-point Likert scale (very necessary, useful and unnecessary). After applying the experts' opinions, the components obtained from the synthesis were presented. Finally, based on the identified components, a template for revising the elementary school math curriculum was presented and 10 experts in the field of curriculum planning and elementary education were asked to express their opinion about this template. Then, the content validity ratio (CVR) was evaluated for each component with the Lausche method. Finding The findings of this research showed that the goals in the revision pattern of the elementary school math curriculum are to achieve in-depth math learning and partial goals include creating and strengthening the six global competencies in students, providing the four elements of learning design, providing learning and teaching conditions, and facilitating the joint research process. Content includes character development, creativity enhancement, critical thinking/ problem-solving enhancement, cooperation enhancement, relationship quality improvement, and social belonging; Learning-teaching strategies including teaching methods, learning partnerships, learning environments, and digital use; Evaluation before teaching, during teaching, evaluation based on the person's performance in life, continuous evaluation and diverse evaluation and joint research process. Grouping should be with a small number and according to the individual differences, needs, and interests of the students. The resources and facilities needed in teaching include equipping the teaching process with facilities and educational technology and empowering teachers. The teaching time should be adjusted according to the volume of the book and the ability of the students, and the teaching place should include a variety of teaching places and a quiet environment. These factors in the form of the presented model have relatively high precision and accuracy. Discussion The purpose of this research was to provide a model for revising the elementary school math curriculum based on Fullan's approach. According to the obtained results, the overall goal of this model is to achieve deep learning, which has been emphasized in numerous domestic studies. The findings of this research showed that this goal can be achieved with four more detailed goals, including creating and strengthening the six global competencies in students, providing the four elements of learning design, providing learning and teaching conditions, and facilitating the joint research process. In line with these results, Fullan has introduced the deep learning model with four layers; The first layer is global competencies that represent the true meaning of deep learning; The second layer represents elements of learning design and includes processes that facilitate change in thinking and action for leaders, teachers, families, and students. The third layer shows the necessary conditions for equipping deep learning at the school, district, and educational system level, which provides solutions in the direction of innovation, growth, and learning culture. The fourth layer is collaborative research which encompasses all layers and a process for continuous improvement of implementation practices. Finally, it should be said that because the math curriculum review model presented in this research is specific to the elementary level, the generalization of the research findings to other subjects and also to other educational levels, have limitations. Therefore, it is suggested that researchers in the field of psychology and educational sciences study to develop a model for revising the curriculum of different branches of mathematics in the secondary education period.